Biodegradable plastics and their impact on fingermark detection methods. (March 2023) - Woodward, Harrison; Moret, Sébastien; Chadwick, Scott
Abstract: The use of plastics is extremely prevalent in society, with most individuals likely to handle several plastic items per day. It is therefore not surprising that many exhibits recovered from the scene of a crime are plastics, which are processed and examined for traces such as fingermarks. Societal trends have been pushing towards more environmentally friendly products with alternatives to traditional disposable plastics becoming increasingly available. These alternate plastics have different chemical compositions and physical properties, which may impact fingermark development for these substrates. As most detection techniques are known to be substrate-dependent, it is crucial to review current methods and procedures to examine how effective they are on new materials. The aim of this research was to assess a range of fingermark detection techniques on biodegradable plastics and provide recommendations for the preferred technique. First, the prevalence of these materials in the Australian market was evaluated. Over 40 different plastics obtained within the Sydney area were then divided into six broad categories using consumer information in combination with ATR-FTIR spectroscopy analysis. Following this, selected plastics from each category were used as substrates for the fingermark development study. In total, 6480 fingermark specimens were collected as split marks, to form 2160 fingermark comparisons. Each substrate was then developed with four fingermark detection techniques suitable for plastic substrates: cyanoacrylate (CA) fuming, vacuum metal deposition (VMD), powder suspensions (PS), and single metal deposition (SMD). SMD resulted in the most consistent development method across all tested substrates. VMD was able to successfully develop fingermarks on polyethylene-based plastics, but led to poorer results on alternative plastics, while CA fuming and PS were notably more dependent on the surface texture. This research was successful in confirming that biodegradable plastics do in fact have an impact on fingermark development techniques commonly applied on traditional plastics and recommendations have been formed to aid in operational contexts to improve the potential to recover latent fingermarks from biodegradable plastics. Highlights: Biodegradable alternatives to traditional plastics are becoming more prevalent. New materials create a gap in fingermark development research. Conventional methods shown to be less effective on new plastics. Single metal deposition is the preferred development method.